New theories of the origin, history and meaning of the word Peru - Alomía-Lucero, José M. (2025)
The etymological origin of the word "Perú" presents historical gaps that have traditionally been attributed to the Spanish. However, the globalization of knowledge and access to new sources allow for the exploration of alternative hypotheses. The study aims to demonstrate that "Perú" has roots in indigenous South American languages, specifically in Amazonian, Tupi-Guarani, Quechua, and other indigenous Amazonian languages. The research uses a basic qualitative approach, with an exploratory descriptive level, utilizing the historical method to analyze documentary and etymological sources. The results reveal that the Amazonian origin is supported by the phonetic similarity with river names such as Pará, Paru, Apere, Purús, Paraná, and Perené. In the Tupi-Guarani context, it is related to terms such as "Peabirú" (road to Birú or Perú), Paraguay, and Uruguay. In Quechua, "Pirwa" or "Pirhua" (corn granary) and "Purutu" (bean) are phonetically parallel. In indigenous Peruvian languages, "Peabirú" is similar to "Abiro" (greeting or "you") and Piro, Piró. These findings suggest that "Perú" is a precolonial term of South American origin.